Region-Based Hough-Inversion Transform for Circles - Destéfanis, Eduardo A. (2003)
The Hough Transform is a robust algorithm, intended to detect lines, circles or even more complex shapes within an image. A weakness of the algorithm is that it requires an important processing time, in particular if the shape to be detected is not a straight line. In many practical applications this constraint could not be acceptable. A solution to this problem has been called the Fast Hough Transform (FHT) -[8] and [5]. The FHT approaches addresses the problem using specialized parallel hardware. Instead of this, this paper proposes an algorithmic approach for circle detection, which yields an acceptable processing time, without the need of any specialized hardware. To reach this goal the inversion transform [2] is used.